Incorporating electrical impedance tomography to transpulmonary pressure-guided PEEP in severe ARDS with pneumothorax and multiple cavitations: a case report - Wang, Qianling; Su, Longxiang; Jiang, Jing; Wang, Na; He, Huaiwu; Long, Yun (Frontiers in Medicine, 2023)
Pneumothorax is a potentially fatal complication in patients with acute respiratory distress syndrome (ARDS), presenting challenges in determining the optimal positive end-expiratory pressure (PEEP) level to prevent atelectasis without exacerbating the pneumothorax. This case report describes the successful application of transpulmonary pressure and electrical impedance tomography (EIT) at the bedside to guide PEEP selection in a patient with ARDS complicated by pneumothorax due to methicillin-resistant Staphylococcus aureus infection. By using minimal PEEP to maintain positive end-expiratory transpulmonary pressure and visualizing lung reopening with EIT, the optimal PEEP level was reaffirmed, even if traditionally considered high. The patient's condition improved, and successful weaning from the ventilator was achieved, leading to a transfer out of the intensive care unit.